2016
DOI: 10.18632/oncotarget.9059
|View full text |Cite
|
Sign up to set email alerts
|

Prevention effect of rare ginsenosides against stress-hormone induced MTOC amplification

Abstract: Stress has been suggested as one of important cause of human cancer without molecular biological evidence. Thus, we test the effect of stress-related hormones on cell viability and mitotic fidelity. Similarly to estrogen, stress hormone cortisol and its relative cortisone increase microtubule organizing center (MTOC) number through elevated expression of γ-tubulin and provide the Taxol resistance to human cancer cell lines. However, these effects are achieved by glucocorticoid hormone receptor (GR) but not by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…We recently developed a technique for the mass production of the rare ginsenoside Rg6 from the ginsenoside Re, which is a main component of ginseng leaves 50 . Using this method, Rg6 was sufficiently prepared, and our group reported its effects on tumorigenesis 51 .…”
Section: Discussionmentioning
confidence: 99%
“…We recently developed a technique for the mass production of the rare ginsenoside Rg6 from the ginsenoside Re, which is a main component of ginseng leaves 50 . Using this method, Rg6 was sufficiently prepared, and our group reported its effects on tumorigenesis 51 .…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, inhibits the activation of proliferative signals in breast cancer cells [ 90 ]. Another study found [ 91 ] that intervention of Rg6 could block cortisol/cortisone-induced deregulation of microtubule organizing centers as well as ER signaling in breast cancer cells, alter stress hormone or steroid hormone-induced chromosomal instability, and inhibit aberrant activation of tumor cell proliferative signaling. The stress hormone cortisol and cortisone have been shown to elevate the expression of γ-tubulin, increasing the number of microtubule organizing centers and promoting resistance to paclitaxel in breast cancer cells.…”
Section: Mechanism Of Action Of Ginsenosides Altering Breast Cancer H...mentioning
confidence: 99%
“…Furthermore, Rg1 [ 120 ] has been demonstrated to inhibit the phosphorylation of histone H3Thr3 mediated by Haspin kinase, leading to an increase in the width of the metaphase plate and spindle instability during cancer cell division, resulting in a delay in the progression of mitotic differentiation and inhibition of proliferation in breast cancer cells. Similarly, intervention with Rg6 [ 91 ] can induce chromosomal instability, which resensitizes paclitaxel-resistant breast cancer cells to paclitaxel treatment.…”
Section: Mechanism Of Action Of Ginsenosides Altering Breast Cancer H...mentioning
confidence: 99%
“…Rg4, a rare ginsenoside, is the main low-polarity protopanaxatriol-type ginsenoside of black ginseng. Recently, the rare ginsenoside Rg4 was shown to exhibit potent antistress, antisubstrate metalloproteinase-13 expression, pulmonary protection, and apoptosis-inducing effects [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%